Structured Literacy: An Effective Approach for All Students (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Learning to read is an essential skill that allows students to increase their knowledge of any topic they desire.  Many students struggle to learn to read and teachers are tasked with the challenge of ensuring all students, including students with reading disabilities, are successful readers.  This paper examines the structured literacy approach as a successful method to teaching all students to read.  It gives a clear description of the components of a structured literacy approach and the benefits it has over using typical literacy practices, such as balanced literacy or whole language approaches, to teach reading. Teachers are responsible for ensuring that all students succeed and are called to advocate for the structured literacy approach in their schools.            Keywords: structured literacy, phonics, explicit & systematic, typical literacy practices
Keywords: structured literacy; phonics; explicit & systematic